Eksplorasi Etnofisika Pada Tari Pamonte Suku Kaili Sulawesi Tengah - Faizah, Husnul; Ratnaningtyas, Delthawati Isti; Miftah, Miftah; Khuzaimah, Andi Ulfah; Syamsu, Syamsu (Al-Khazini, 2025)
The cultural diversity of the Kaili tribe holds significant potential for ethnophysics research. However, ethnophysics studies within the Kaili tribe’s culture remain limited. This study aims to explore ethnophysics in the movements and props of the Pamonte dance of the Kaili tribe in Central Sulawesi. Data collection techniques used in this study include observation, interviews, and documentation. The research data were analyzed using the Miles and Huberman data analysis model, which consists of data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the Pamonte dance applies physical principles such as normal force, friction force, muscle force, thrust force, and Newton's laws. Additionally, concepts of potential energy, kinetic energy, velocity, and acceleration are evident in the dancers' body positions when bending, lifting, or walking according to the floor pattern. Concepts of torque, moment of inertia, pressure, translational motion, rotational motion, impulse, and momentum are also reflected through the dancers' movements and interactions with dance props such as toru.